A processualidade da aprendizagem e do ensino na educação superior: um estudo comparado internacional no campo da educação especial - Conceição, Junio Hora (2022)
This works intends to establishes comparatives studies between two public universities from two countries: The University of Guadalajara (UdeG), in Mexico, and the Federal University of Espírito Santo (UFES), in Brazil, in order to analyze the processes of learning and teaching of special education students of in Higher Education. That way, we investigate how and why humanistic, didactic-pedagogical and administrative investments influence the learning process of students who are the special education students in Higher Education. About humanistic investment we refer to any inclination towards actions that produce tolerance and sympathy, in the search for the continuity of the civilizing process. Regarding to the didactic pedagogical investments, we deal with those that are based on humanistic investments to think about inclusive teaching practices. However, through of a society based on the contemporary industrial context, these issues need to be surrounded, too, by an investment that makes the democratic management of the education space, therefore the importance of administrative investment, in order to organize the applicability of legislation and public politics in the practical context of schooling. For the development of this research, we are supporting the theories of professor Paulo Freire (2018; 2020) and sociologist Norbert Elias (1993; 2011). The first, given its scope in the context of thinking about Education as an act of resistance in the face of social injustice, from its incursions, not only in Brazil, but in Latin America, the United States, Europe and Africa. Places that provided us with countless sócio philosophical actions and reflections on our (in)conclusion as individuals, while the second for his analyzes of the ways in which we have developed our Civilizing Process: exactly as something continuous, unfinished. We use methodologies and technical resources such as interviews with students and professors, as well as document analysis to the development of this research, in order to highlight inclusive practices produced in the relationship between professors and students. The results indicate that this conjuncture of elements that we were able to categorize contribute to Special Education in Higher Education, in an international perspective, with Mexico and Brazil, UdeG and UFES, expanding their perspectives of inclusion, so that these students have their rights guaranteed. Although we still lack a lot, we continue in the civilizing process carried by the unfinished that makes us human.